Descarte de resíduos hospitalares de um hospital veterinário localizado na cidade de Araguaína: - Santana, Yasmin Morais (Universidade Federal do Tocantins, 2023)
Reverse logistics encompasses possibilities for the preservation of biodiversity, reducing the harm generated by the incorrect disposal of everything that is discarded. Solid health waste requires special attention, as some can be reused and others need separate segregation from those that we are not aware of. However, emphasis is placed on the importance of reverse logistics in health service providers, such as hospitals, veterinary clinics, beauty centers, tattoo studios, pharmacies, among others. The objective of the research is focused on the disposal of hospital waste from a veterinary hospital located in Araguaína/TO, specifying the groups according to Anvisa criteria and preparing an educational booklet informing the respective types of waste and alerting care in handling and packaging. The study is a case study, with a deductive-qualitative method of approach with monographic procedures, documental research technique, in sources such as public and private archives. As an analysis and results, an educational booklet was prepared that basically is a synthesis of the information described in this article. The booklet proposes, in a didactic and practical way, which are the groups of health waste, what they are and what are the correct methods of packaging each waste and tailings. It is concluded that this article establishes practices to raise awareness of the disposal of solid health waste, the preservation of the environment and the conservation of the health of all employees is crucial for the quality of the establishment's services.